Learning from the First Citizen Science Association Virtual Conference - Abigail Hils; Skye Kelty; Angel Hjarding; Linda Silka; Alison Cawood (Citizen Science: Theory and Practice, 2023)
The Citizen Science Association (CSA) is a member-driven organization that connects people with interest in community/citizen science (c*science) from a wide range of backgrounds, disciplines, and experiences. In response to the COVID-19 pandemic, the bi-annual CSA conference pivoted away from an in-person format to a virtual format. 'CitSciVirtual: Local, Global, Connected' occurred throughout May 2021 and brought together more than 700 attendees from 36 countries. The conference prioritized interactive experiences for attendees, including 16 collaborative poster sessions featuring 240 virtual posters, 55 workshops to learn and practice new skills, and 7 social events. This paper summarizes the impacts of the rapid transition to a virtual format on the conference goals, planning and decision-making processes, practices, outcomes, and attendee experiences. Both the strengths and weaknesses of this first virtual conference are featured to outline opportunities for growth for the CSA, c*science at large, and science conferences in general.